The Relationship Between Midwife Performance With Antenatal Care (Anc) Service Satisfaction At Telagasari Community Health Center, 2023 - Melda Iskandar; Titin Eka Sugiatini (CV. Inara, 2024)
One of the midwifery services performed by midwives is antenatal examination, namely pregnancy examinations carried out to periodically check the condition of the mother and fetus, followed by efforts to correct deviations found. Antenatal care plays an important role in efforts to prevent (preventive) and reduce MMR and IMR. Midwifery services contribute to implementing quality antenatal care according to standards. So that every effort to improve quality must also be accompanied by efforts to improve the performance of each officer, especially midwives. Research Objectives: To determine the relationship between the performance of midwives and the satisfaction of ANC services at the Telagasari Health Center in 2023. Research Methods: This type of research is descriptive analytic with a cross sectional design. The sample of this research were 76 pregnant women. The sample technique uses accidental sampling technique. Data collection using a questionnaire. The data analysis used was univariate analysis and bivariate analysis using the chi square test Research Results: The results of the study show that a p-value of 0.000 is obtained, meaning that the p-value <0.05 can be concluded that Ha is accepted and Ho is rejected. This means that there is a very strong and one-way significant relationship between the performance of midwives and the satisfaction of ANC services for pregnant women at the Telagasari Health Center. Conclusion: There is a relationship between the performance of midwives and satisfaction with antenatal care (ANC) services at the Telagasari Health Center in 2023.